Pengembangan Lembar Kerja Peserta Didik (LKPD) Materi Penyelesaian SPLDV dengan Metode Grafik Berbasis Realistic Mathematics Education (RME) - Mauludiana Nur Islamiyah; Evangelista Lus Windyana Palupi (Universitas Negeri Surabaya, 2026)
The ability to create, read, and analyze data from graphs in everyday life makes mastery of the graphical method of System of Linear Equations in Two Variables (SLETV) important. This research aims to describe the validity, practicality, and effectiveness of an RME-based student worksheet on SLETV solving using the graphical method. This research utilizes the ADDIE model, a development research approach that involves analysis, design, development, implementation, and evaluation. The developed student worksheet was designed based on the four-level iceberg levels, where students solved contextual problems related to vehicle speed at the situational level, determined the speed and travel time of each vehicle at the model-of level, determined whether one vehicle could overtake another at the model-for level, and identified the types of SLETV solutions based on graphs at the formal level. The results of the student worksheet development were tested on 30 students of class VIII at SMPN 15 Surabaya. The results showed that the developed student worksheet was very valid (4.51), with the content aspect obtaining the highest score and the time aspect the lowest; practical (4.3), with the preliminary aspect obtaining the highest score and the closing aspect the lowest; and effective, as reflected by student activity rates of 91.77% and 94.12%, a positive response rate of 83.14%, and an N-Gain score of 0.48, indicating moderate improvement in learning outcomes. Therefore, the developed RME-based student worksheet can be used in mathematics learning and helps students solve SLETV problems using the graphical method through the four iceberg levels.